Endothelial nitric oxide synthase (eNOS) gene polymorphism (Glu298asp) and nitric oxide (NO) levels in patients with ST-segment elevation myocardial infarction (STEMI) - Mohit Dayal Gupta; Cherian Akkarappatty; Shekhar Kunal; Girish MP; Ankit Bansal; Vishal Batra; Sanjay Tyagi (Indian Heart Journal, 2024)
Background: Genetic polymorphism in endothelial Nitric Oxide Synthase (eNOS) are associated with occurrence of multiple cardiovascular diseases (CVDs). Methods: This study included 300 young ST-segment elevation myocardial infarction (STEMI) patients and 300 healthy controls. STEMI patients were divided into two groups: premature coronary artery disease [CAD] (STEMI<40 years of age) and older STEMI (>40 years of age). Genetic polymorphisms in the eNOS gene (894G/T) was evaluated in both subjects and controls. Plasma levels of nitric oxide (NO) were estimated for both patients as well as controls. Results: Mean age of the study population was 49.7 ± 9.2 years with premature CAD being present in 58 (19.3 %) patients. No significant difference at genotypic (P = 0.589, odds ratio (OR) = 0.9, 95 % CI = 0.6–1.6) and allelic level (P = 0.173, OR = 1.2, 95 % CI = 0.9–1.4) was observed between STEMI patients and healthy controls. Genotype 894 TT had significantly higher frequency in STEMI patients >40 years (P = 0.047, OR: 2.5; 95 % CI = 1.0–6.0). No significant difference at genotypic (P = 0.279) and allelic level (P = 0.493) was observed between premature CAD (STEMI age <40 years) and healthy controls. NO levels (131 ± 59.6 μM vs 118.11 ± 49.96 μM; P = 0.001) was significantly higher in healthy controls as compared to STEMI patients >40 years of age (P= 0.001). Conclusion: There was significant association of eNOS gene polymorphism Glu298Asp with STEMI patients > 40 years. However, this association was not observed in premature CAD patients. Lower levels of NO in STEMI patients >40 years suggests its potential role as a marker of CVD.